P*-closure operator and p*-regularity in fuzzy setting - Bhattacharyya Anjana (Mathematica Moravica, 2015)
In this paper a new type of fuzzy regularity, viz. fuzzy p*- regularity has been introduced and studied by a newly defined closure operator, viz., fuzzy p*-closure operator. Also we have found the mutual relationship of this closure operator among other closure operators defined earlier. In p*-regular space, p*-closure operator is an idempotent operator. In the last section, p*-closure operator has been characterized via p*-convergence of a fuzzy net.